English as a Foreign Language (EFL) Student Teachers' Readiness to Deal with Online Learning During the Covid-19 Pandemic - Aprilia Sari, Evi Nusrira; Azkiyah, Siti Nurul; Sumintono, Bambang (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2021)
AbstractThe COVID-19 pandemic has forced all teachers to deliver online teaching and learning whether they are ready or not. Some studies have reported that many teachers face many challenges in delivering online classrooms. Hence, it is logical to assume that student teachers are likely to face even a more complex situation dealing with this issue. Unlike in-service teachers, for student teachers, they lack experience in both face-to-face and online learning. Therefore, this study attempts to report the readiness of English as a Foreign Language (EFL) student teachers and the kinds of digital competencies they need to be ready to teach English with digital technology using a quantitative approach. There were 60 respondents who participated using convenience sampling, from an Islamic university in Bogor, Indonesia. Using the TESOL Technology Standards for Teachers and Technology Acceptance Model (TAM) theory, a questionnaire consisting of 50 items was written in 'yes' and 'no' questions. The findings of the study show that most respondents possess adequate basic digital skills to teach digital technology. However, they need to learn various digital technology that more effectively supports language instructions.The respondents also indicate acceptance of the utilization of technology and are willing to integrate it into their future classrooms. This study implies the need to include technology in the curriculum of the English Education Department.AbstrakPandemi COVID-19 telah memaksa semua guru untuk melaksanakan belajar mengajar secara online baik siap atau tidak. Beberapa penelitian telah melaporkan bahwa banyak guru menghadapi banyak tantangan dalam memberikan ruang kelas online. Oleh karena itu, masuk akal untuk mengasumsikan bahwa siswa guru cenderung menghadapi situasi yang lebih kompleks dalam menangani masalah ini. Tidak seperti guru yang sudah mengajar, mahasiswa, kurang pengalaman dalam pembelajaran tatap muka dan online. Oleh karena itu, penelitian ini mencoba melaporkan kesiapan siswa guru Bahasa Inggris sebagai Bahasa Asing (EFL) dan jenis kompetensi digital yang mereka butuhkan untuk siap mengajar Bahasa Inggris dengan teknologi digital menggunakan pendekatan kuantitatif. Ada 60 responden yang berpartisipasi menggunakan convenience sampling, dari sebuah universitas Islam di Bogor, Indonesia. Menggunakan teori TESOL Technology Standards for Teachers and Technology Acceptance Model (TAM), kuesioner yang terdiri dari 50 item ditulis dengan pertanyaan 'ya' dan 'tidak'. Temuan penelitian menunjukkan bahwa sebagian besar responden memiliki keterampilan digital dasar yang memadai untuk mengajarkan teknologi digital. Namun, mereka perlu mempelajari berbagai teknologi digital yang lebih efektif mendukung pengajaran bahasa. Responden juga menunjukkan penerimaan pemanfaatan teknologi dan bersedia mengintegrasikannya ke dalam kelas masa depan mereka. Studi ini menyiratkan perlunya memasukkan teknologi ke dalam kurikulum Departemen Pendidikan Bahasa Inggris. How to Cite: Sari, E.N.A., Azkiyah. S.N., Sumintono, B. (2021). English as a Foreign Language (EFL) Student Teachers' Readiness to Deal with Online Learning During the Covid-19 Pandemic. TARBIYA: Journal of Education in Muslim Society, 8(2), 135-154. doi:10.15408/tjems.v8i2.23324.